Censorship: Media/CSO websites, Proton VPN (Venezuela) - Voidly (Voidly Global Censorship Index, 2024)
CRITICAL severity censorship detected in Venezuela. Data sourced from CensoredPlanet.
Censorship Incident ID: VE-2024-0002. Severity: critical. Confidence: 75%